Xanthan gum hydrogel wound dressing enhances wound healing in a rat excisional injury model - Seyyedeh Sahra Mirmasoudi; Zahra Pourmohammadi-Bejarpasi; Mohsen Shahrousvand; Mehryar Habibi Roudkenar (Heliyon)
Skin wounds are a public health concern due to limited effective natural remedies. This study aimed to develop and evaluate a novel wound dressing hydrogel composed of polyacrylic acid (PAA) and xanthan gum (XG) using a rat excisional injury model. The hydrogel was synthesized via free radical polymerization, employing potassium persulfate (KPS) as an initiator and N,N-methylene bisacrylamide (MBA) as a crosslinker. Morphological characterization was performed using Scanning Electron Microscopy (SEM), Fourier-transform Infrared Spectroscopy (FTIR), and Thermogravimetric Analysis (TGA). Swelling and deswelling tests identified the optimal formulation containing 1 % XG, which exhibited enhanced swelling ratios, mechanical strength, and controlled release properties. In vivo studies demonstrated that this hydrogel formulation significantly improved wound contraction and healing rates in comparison to controls, showing excellent biocompatibility and non-toxicity. These results suggest that combining natural biopolymers like xanthan gum with synthetic polymers offers a promising new approach for wound care. Further studies, including clinical trials, are warranted to validate the therapeutic potential of this xanthan gum-based hydrogel dressing.